2023
DOI: 10.3390/app13074342
|View full text |Cite
|
Sign up to set email alerts
|

Equalization of the Occlusal State by Wearing a Mouthguard Contributes to Improving Postural Control Function

Abstract: The aim of this study was to clarify the effect on the postural control function of equalizing the occlusal contact state by wearing a mouthguard. Method: Participants included 23 untrained adults, 11 gymnasts, and 10 weightlifters. Custom mouthguards were fabricated and adjusted so that all teeth were in even contact with light clenching. The standing postural control function was evaluated by the displacement of the center of foot pressure (COP) measured using a gravity center fluctuation meter. Measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Therefore, it is possible that there was no significant difference between ICP and MG during clenching. It has been reported that individuals with good occlusal balance tend to have a more stable center of gravity than those with poor occlusal balance, and that wearing a mouthguard stabilizes the center of gravity for those with poor occlusal balance (Bando et al, 2019;Takahashi et al, 2020Takahashi et al, , 2023a). In the future, it will be necessary to investigate the relationship between clenching and spinal alignment due to occlusal balance, and to compare the effects of wearing a mouthguard in greater detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible that there was no significant difference between ICP and MG during clenching. It has been reported that individuals with good occlusal balance tend to have a more stable center of gravity than those with poor occlusal balance, and that wearing a mouthguard stabilizes the center of gravity for those with poor occlusal balance (Bando et al, 2019;Takahashi et al, 2020Takahashi et al, , 2023a). In the future, it will be necessary to investigate the relationship between clenching and spinal alignment due to occlusal balance, and to compare the effects of wearing a mouthguard in greater detail.…”
Section: Discussionmentioning
confidence: 99%
“…A single-layer mouthguard was fabricated using a 2.0-mm-thick thermoplastic sheet (Sports Mouthguard; Keystone Industries, Cherry Hill, NJ) and a pressure molding machine (Model Capture Try; Shofu Inc., Kyoto, Japan). The amount of occlusal elevation was set within the range of the resting space, and all teeth were adjusted to make even contact upon light clenching (Takahashi et al, 2020(Takahashi et al, , 2023a.…”
Section: Mouthguard Fabricationmentioning
confidence: 99%
“…In addition, the main cause is thought to be the appropriate classification of the two groups according to the state of occlusal contact. Previous research has revealed that the outer peripheral area and unit area trajectory length are affected by occlusal balance in the evaluation of postural stability, using static center-of-gravity sway as an index (Takahashi et al, 2020(Takahashi et al, , 2023b. In other words, the group with good occlusal balance has a smaller center of foot pressure displacement and a superior postural control function.…”
Section: Discussionmentioning
confidence: 99%
“…The participant was placed in a sitting position, the pressure-sensitive film was inserted into the mouth so that the occlusal plane was parallel to the floor, and the participant was instructed to clench their teeth at maximum intensity for 3 s in the intercuspal position. After that, the pressure-sensitive film was taken out of the mouth and analyzed using the dedicated analyzer (Takahashi & Bando, 2018;Takahashi et al, 2023aTakahashi et al, , 2023bTakahashi et al, , 2023c. The distribution of the occlusal contact area on the left and right sides is displayed by the dedicated analyzer.…”
Section: Measurement Of Occlusal Contact Statementioning
confidence: 99%
See 1 more Smart Citation